The Persistence of Long-Run Abnormal Returns Following Stock Repurchases and Offerings - FU, Fangjian (Institutional Knowledge at Singapore Management University, 2015)
The long-run abnormal returns following both stock repurchases and seasoned equity offerings disappear for the events in 2003–2012. The disappearance is associated with the changing market environment: increased institutional investment, decreased trading costs, improved liquidity, and enhanced regulations on corporate governance and information disclosure. In response to the more efficient pricing of stocks, firms become less opportunistic in stock repurchases and offerings. Recent events of stock repurchases and offerings are motivated more by business-operating reasons than to exploit mispricing. Both external market factors and internal firm factors contribute to the disappearance of the postevent abnormal returns. Our findings on the recent events contrast with those of earlier studies and shed light on how the changing market environment affects both asset pricing and corporate behavior.